Standing at the crossroads: the vulnerabilities of Australian business schools. Issue 6 (23rd August 2020) - Hogan, Owen; Kortt, Michael A.; Charles, Michael B.
Abstract : Purpose: To identify key factors that are contributing to vulnerability in business schools in Australian public universities and determine the degree of vulnerability exhibited by these schools. Design/methodology/approach: Using a multi-criteria assessment (MCA) approach, a framework is developed to determine which business schools are most vulnerable to disruptions and uncertainty. Findings: The findings show a lack of preparedness on the part of many business schools, particularly those relying heavily on international students. Practical implications: The implication is that business schools in Australian public universities need to diversify revenue streams and continue to seek legitimacy through external stakeholders such as employers and international accrediting bodies. Originality/value: This study presents an empirical perspective of business schools in Australian public universities and offers valuable insights for university leaders and policymakers.